Studies on the livestock of southern Darfur, Sudan. VIII. A comparison of productivity indices for goats and sheep - Wilson, R.T. (Springer, 1983)
Presents results of a least-squares analysis of the variance in three indices of productivity, viz. liveweight of young weaned per breeding female, per kg. of breeding female and per kg. metabolic weight of female, due to sex of offspring, parity, type & season of birth, system of production (sedentary/transhumant) and flocks within systems for both sheep & goats in Southern Darfur, Sudan. Compares the productivity of the two species and identifies factors having significant effects.